Peran Lembaga Al-Islam Kemuhammadiyahan Dalam Mengkomunikasikan Citra Kampus Islami - Khansa Alifatun Nabila; Putri Vania Iftatunnisa; Anggita Candra Adnaneswari; Ainun Nusharatillah Al Falah; Tria Patrianti (Jurnal Budi Pekerti Agama Islam, 2024)
Al-Islam Kemuhammadiyahan (AIK) serves as a platform for students at the University of Muhammadiyah Jakarta to learn about Kemuhammadiyahan and religious practices. In its implementation, the AIK institution also serves as a medium to instill the values of an Islamic campus, as stipulated in the Rector's Decree no. 446/R-UMJ/VII/2023 regarding the application of the AIK Curriculum and Islamic Campus. The AIK institution also provides a space for students at the University of Muhammadiyah Jakarta to submit their memorization, which is a requirement for their thesis defense. However, in its implementation, some students encounter challenges in submitting their memorization, both due to internal and external factors. This research aims to examine the image of the Al-Islam Kemuhammadiyahan institution for students at the Faculty of Social and Political Sciences (FISIP) UMJ and to analyze the role of this institution in communicating UMJ's positive image as an Islamic campus. This research employs a qualitative research method with a descriptive approach. The data collection techniques used include interviews as well as gathering secondary and primary data. The findings of this research reveal that AIK plays.